Aspectos da Natureza da Ciência nos discursos de futuros professores de ciências frente a questões sociocientíficas - Jesus, Atair José Bernardino de (2020)
The notions produced from investigations about the intrinsic issues of Science are understood within a specific field of study called Nature of Science (NOS) that is closely related to the teaching of Science in the school environment. Thinking of the current conjuncture, in which different degrees form the professionals who work in the teaching of Sciences, our work was organized as a reflexive effort that aimed to investigate the speeches of students of the Biological Sciences and Pedagogy courses at the State University of the West of Paraná campus Cascavel-PR in its last year of formation. So, our research problem materialized in the following question: What aspects of the Nature of Science are present in the discourse of Biological Sciences and Pedagogy students when confronted with science teaching content that are permeated by scientific controversies? Of a qualitative nature, the core of this work ended by conducting semi-structured interviews and with regard to data analysis, we find in the Discourse Analysis of French designation (ORLANDI, 1999, 2007; FREIRE, 2014) the way to investigate the positions contained in the interviewees' speeches. Turning our look to the speeches of each subject individually, and also to the relationship between them, we aim with the present work to problematize aspects of the Science vision of future Science teachers participating in the research in relation to Science teaching themes that are permeated by controversies. In this perspective, our analytical activity used as a basis the aspects of NOS pointed out by Douglas Allchin (2013) as well as the discussion with other authors that pervade this theme. In summary, the interviewees understood the concept of controversy as: Contradictory aspect; Contradiction between Religion and Science; Contradiction between Science and Common Sense. On the agribusiness socio-scientific theme, positions emerged related to: Defense of use; Combat use, Balance between the positive and negative points of use; and even the understanding that the positioning within the discussion depends on the position that the subject occupies in society. As for the production of hydroelectric energy, the speeches were divided into two main positions: Defending alternative forms of energy with less impact and highlighting the positive and negative points of hydroelectric energy. Reflecting on the partial inventory of the NOS by Douglas Allchin (2013) and the positions of the interviewed subjects, the relationship established between the socio-scientific controversies and the Sociocultural dimension, with regard to credibility, the role of cultural beliefs, ideology and religion, and a credibility of several scientific journals and media. We realized at the end of the present research, that even on a small scale, we built a space for discussion together with the interviewed subjects, leading them to reflect on the controversial potential existing within the science content that will be worked on by them inside the classroom.